1990
DOI: 10.1080/00021369.1990.10870409
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Dimethyl Sulfoxide as a Solvent in Bioassay System with HeLa Cells Evaluated Colorimetrically with 3-(4,5-Dimethyl thiazol-2-yl)-2,5-diphenyl-tetrazolium Bromide

Abstract: The toxicity of dimethyl sulfoxide (Me2SO) was examined in HeLa cells cultured at 37 degrees C for up to 72 hr. The growth of the cells was measured by a colorimetric method with the use of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), which gave good correlation between the cell number and the color development from the reduction of MTT under suitable conditions. When the initial number of cells was 3 x 10(4)/ml, Me2SO at 1% or less had no apparent effect on proliferation for up to 48 hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 1 publication
0
30
0
Order By: Relevance
“…These samples were dissolved in dimethyl sulfoxide (DMSO; Rankem, India), which was then diluted with DMEM. The concentration of DMSO in the test samples was kept at 1% …”
Section: Methodsmentioning
confidence: 99%
“…These samples were dissolved in dimethyl sulfoxide (DMSO; Rankem, India), which was then diluted with DMEM. The concentration of DMSO in the test samples was kept at 1% …”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the amount of carrier solvent used should not exceed 0.5% of the total solution to eliminate interference or toxicity due to the presence of excess carrier solvent (Bradlaw and Casterline, 1979;Harris et al, 1989). Trivedi et al (1990) examined the toxicity of DMSO to the human carcinoma cell line HeLa. When the initial number of cells plated was 3 × 10 4 /ml, DMSO concentration of 1% or less had no apparent effect on the rate of proliferation for up to 48 h of incubation at 37 • C. In incubations up to 72 h, cell growth was repressed by 1% DMSO.…”
Section: Dosing and Incubationmentioning
confidence: 99%
“…The compounds were assayed as dimethyl sulfoxide (DMSO) solutions at the following concentrations: 5, 12.5, 25, 50, 100 μM, against gefitinib as a reference standard. DMSO was used as a negative control of choice since it has been found before to have no apparent effect on proliferation of the HeLa, Caco-2, and C3A cells at 1% or less for up to 48 h [22,23]. Gefitinib used as a positive control, on the other hand, has previously been found to induce autophagy in lung cancer A549 cells and to enhance apoptosis and suppress cancer cell proliferation [2].…”
Section: Resultsmentioning
confidence: 99%